The Six Lessons of Mises: a reflection of Public Policies in Times of Pandemic - Silva e Meirelles, Dimária (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2021)
From the perspective of the market as a process, the market only exists to the extent that exchanges take place. So, what is better in times of social isolation: intervene to ensure that the market works or let the market freeze freely? Moreover, to what extent is it possible to intervene in the market in times of pandemic, preserving the principles of economic freedom? Based on the principles of cooperation and economic calculation proposed by Mises, the objective of this paper is to analyze the possibilities of public policy in a situation of social isolation. Among the main public policy devised in this time of the pandemic, the following measures have provided the continuity of the market process: credit, tax deferrals, and emergency assistance or paycheck protection program. The concern with the preservation of the economic calculation extends to all supply chain linkages, including final customers, for to companies continue to do their economic calculation.